Rancang Bangun Aplikasi Panduan Peduli Jemaah Haji (APPJI) Berbasis Android - Estu Sinduningrum; Mita Permatasari; Ahmad Rizal Dzikrillah (Universitas Islam Sumatera Utara, 2021)
Hajj is one of the 5 pillars of Islam. In performing the pilgrimage, there are many problems and obstacles that are often experienced by pilgrims, including: the number of pilgrims who still need guidance regarding Hajj materials and various supporting features as well as many pilgrims who are still often left behind from their entourage, this makes it easy for pilgrims to perform Hajj. lost or separated from his hajj tour group. The purpose of this research is expected to be able to help pilgrims to overcome the problems that often occur by implementing the location sharing feature with Google Maps integration for tracking using GPS so that pilgrims can send accurate locations of their whereabouts. This application uses the Waterfall development method, UML as the design design. This research has produced an android-based application called APPJI (Application Peduli Jamaah Haji) that can be used for Mobile Android Smartphones with 89.2% of test results stating that the application has met the software's ideal score.